Den and Cat: Approaches to One Single Cajamarcan Language - Torres Menchola, Denis (2024)
The objective of this paper is to offer an insight on two hypothetical languages from the department of Cajamarca, Peru, named den and cat, whose existence was postulated based on toponymy. From a georeferenced database, a set of toponyms from the department was selected, in which the segments <den> and their variants, associated to the den language, and <cat> and <can> and their variants, linked to the language cat, were identified. The names were cartographically visualized using a geographic positioning system that allowed their exact location based on the use of georeferenced coordinates. The distribution of the toponyms with the three segments allows to assert with confidence that they are part of the same linguistic entity.